Comparison of patients diagnosed with gonorrhoea through community screening with those self-presenting to the genitourinary medicine clinic. Issue 3 (14th March 2014) - Cook, Penny A; Evans-Jones, John; Mallinson, Harry; Wood, Martyn; Alloba, Fath; Jones, Kathy; Strodtbeck, Sara; Hanna-Bashara, Layla
Abstract : Objectives: To compare the clinical, socioeconomic and demographic characteristics of individuals diagnosed with Neisseria gonorrhoeae (NG) in the community using a concomitant nucleic acid amplification test (NAAT, AptimaCombo2) as part of the (community-based) UK Chlamydia Screening Programme (CSP), with those diagnosed in hospital-based genitourinary medicine (GUM) services. Design: A retrospective case note review of all 643 patients treated for NG at a GUM in north west England (January 2007–April 2009). Participants: All 643 treated for NG (including CSP cases, since all cases were referred to GUM for treatment). Limited data were available for 13 CSP cases who failed to attend GUM. Primary outcome measure: Whether the case was detected in the community or GUM services. Predictors were demographics (age, gender, postcode for deprivation analysis), sexual history (eg, number of partners) and clinical factors (eg, culture positivity). Results: 131 cases were diagnosed by CSP (13 of whom did not attend GUM). A further four cases were contacts of these. The GUM caseload was thus inflated by 23% (from 521 to 643). Community cases were overwhelmingly female (85% vs 27% in GUM, p<0.001) and younger (87% females were <25 years vs 70% GUM females, p=0.001). Logistic regression analysis restricted to the target age of the CSP (<25 years) revealed that CSP cases, compared with GUM cases, were more likely to reside in deprived areas (adjusted OR=5.6, 95% CI 1.4 to 21.8 and 5.3, CI 1.7 to 16.6 for the most and second most deprived group respectively, compared with the averagely deprived group, p=0.037) and be asymptomatic (adjusted OR=1.9, CI 1.1 to 3.4, p=0.02). Conclusions: Community screening for NG led to a 79% increase in the number of infections detected in women aged <25 years. Screening is targeted at young people, and tends to disproportionately attract young women, a group under-represented at GUM. Screening also contributed further to case detection in deprived areas.